Effects of wind farms on near-surface wind speed. Issue 5 (February 2019) - Xin, Zhang; Ruiping, Yin; Xu, Ronghui; Jing, Liu; Jingli, He; Yanping, Liu; yongsheng, Wu; Xu, Sun; Lixia, Wang
Abstract: Large-scale development of wind farm has brought environmental benefits, at the same time, it will also affect local meteorological environment. We choose Zhurihe wind farm, which is located in Sonid Youqi of Inner Mongolia, as our study area. Our Observation instrument is HOBO automatic meteorological station. The observation points are set on upwind area, inner wind farm and downwind area, in order to parallelly observe wind speed of 0.5m, 1.5m and 3.0m height. The results show that the wind farm consumes wind energy and reduces wind speed of inner wind farm and downwind area. The relationship of average wind speed in spring, summer and autumn is upwind area> downwind area > inner wind farm. Compared with upwind area, the decrease scope of average wind speed of inner wind farm and downwind area in spring is 5%-22%, summer is3%-25%, autumn is 5%-33%. The influence of wind farm on the near surface wind speed reduces with the increase of environment wind speed in the same season. The existence of the wind farm has no effect on the form of wind velocity profile, which are all the standard logarithmic curve. But the slope of wind velocity profile of inner wind farm and downwind area is decrease. That is to say the fluctuation trend of wind speed increasing with the increase of height is not significant. In addition, compared with upwind area, the existence of wind farm has increased the surface roughness of the area where the wind farm is located in.